Satisfaction with chosen educational paths among Polish and Czech students - Weronika Karaś; Daniel Kukla (Journal of Modern Science, 2025)
Objectives Satisfaction with education is an essential part of the educational process. It should be present at every stage of education, including academic education. By experiencing satisfaction in the education, a person is likely to feel more motivated to realise his or her own educational and professional goals. The aim of this article is to present a study on individually satisfaction with education among Polish and Czech students.